2015
DOI: 10.1002/anie.201412249
|View full text |Cite
|
Sign up to set email alerts
|

Organoaluminum‐Mediated Direct Cross‐Coupling Reactions

Abstract: We present a direct cross-coupling reaction between arylaluminum compounds (ArAlMe2 ⋅LiCl) and organic halides RX (R=aryl, alkenyl, alkynyl; X=I, Br, and Cl) without any external catalyst. The reaction takes place smoothly, simply upon heating, thereby enabling the efficient and chemo-/stereoselective formation of biaryl, alkene, and alkyne coupling products with broad functional group compatibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 64 publications
0
28
0
Order By: Relevance
“…[3] For example, they are utilised in CÀC cross coupling chemistries, and in deprotonative metalation. [4] Catalytic hydroelementation reactions have also witnessed impressive progress in the past few years. Roesky and coworkers demonstrated that a b-diketiminato stabilised aluminium hydride complex is an excellent catalyst for hydroboration of alkynes and carbonyl groups.…”
mentioning
confidence: 99%
“…[3] For example, they are utilised in CÀC cross coupling chemistries, and in deprotonative metalation. [4] Catalytic hydroelementation reactions have also witnessed impressive progress in the past few years. Roesky and coworkers demonstrated that a b-diketiminato stabilised aluminium hydride complex is an excellent catalyst for hydroboration of alkynes and carbonyl groups.…”
mentioning
confidence: 99%
“…Uchiyama et al. carried out direct reaction between arylaluminum compounds and organic halides . Ingleson described transition‐metal‐free reaction of diaryl zinc reagents with alkyl halides .…”
Section: Optimization Of the Reaction Conditions[a]mentioning
confidence: 89%
“…On the other hand, transition‐metal‐free reactions are attracting more and more attention because they are less costly and more environmentally friendly and can avoid any transition metal impurities in pharmaceutical products . For example, Hayashi et al.…”
Section: Optimization Of the Reaction Conditions[a]mentioning
confidence: 93%
“…Consequently, TM‐free cross‐coupling methods have attracted much attention in recent years . Some elegant direct cross‐coupling reactions between organometallics (R–M) and organohalides (R–Hal) have been developed, in which R–M (such as Mg, Zn, Al, and Sn,) reacts efficiently with various types of organohalides, including R–I, R—Br, and even unreactive R–Cl (Scheme a). The mechanisms of these direct cross‐coupling reactions have been clarified by means of both experimental and theoretical methods.…”
Section: Methodsmentioning
confidence: 99%